Indonesian EFL Teachers' Conceptions of Critical Thinking - Ilyas, Hamzah Puadi (Journal of ELT Research, 2018)
This study aims to investigate the Indonesian EFL (English as a Foreign Language) teachers’ conceptions of critical thinking. 59 teachers coming from three different provinces (Jakarta, Banten, West Java) in Indonesia participated in this study by answering open-ended questionnaire. The questionnaire asked two questions. The first question asked whether the participant recognised the term ‘critical thinking.’ The second question asked how the participant conceptualised critical thinking. The study found that only one teacher who never heard the term critical thinking. With regard to the conceptions of critical, there were some emerging themes such as analysis, evaluation, criticism, creativity, problem solving, reflection, curiosity, and even Bloom’s taxonomy. Findings of this study are similar to the critical thinking conceptions proposed by Western academics.